The other half of my heart - Frazier, Sundee Tucker, 1968- (Delacorte Press, 2010)
Twin daughters of interracial parents, eleven-year-olds Keira and Minna have very different skin tones and personalities, but it is not until their African American grandmother enters them in the Miss Black Pearl Pre-Teen competition in North Carolina that red-haired and pale-skinned Minna realizes what life in their small town in the Pacific Northwest has been like for her more outgoing, darker-skinned sister.